2015
DOI: 10.1007/s10554-015-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased left atrial size is associated with reduced atrial stiffness and preserved reservoir function in athlete’s heart

Abstract: Left atrial (LA) fibrosis with increased stiffness has been assumed to be the substrates for occurrence of atrial arrhythmias in athletes. However, this hypothesis has not yet been confirmed in humans. Aim of this study was, therefore, to assess LA remodeling and stiffness in competitive athletes. 150 competitive athletes and 90 age and sex-matched sedentary subjects were analyzed by speckle-tracking echocardiography to measure peak atrial longitudinal strain (PALS) and peak atrial contraction strain (PACS). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
(60 reference statements)
4
30
1
2
Order By: Relevance
“…A significantly lower mitral inflow pulsed-wave late diastolic filling (A-wave) peak velocity in the athletes group confirms that in athletes the reservoir and conduit function of the LA predominates. The same effect was observed in the study by D'Ascenzi et al [56] of 150 athletes compared to 90 matched controls.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 84%
See 1 more Smart Citation
“…A significantly lower mitral inflow pulsed-wave late diastolic filling (A-wave) peak velocity in the athletes group confirms that in athletes the reservoir and conduit function of the LA predominates. The same effect was observed in the study by D'Ascenzi et al [56] of 150 athletes compared to 90 matched controls.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 84%
“…The blood flow meets almost no resistance because of good compliance, and the LV filling pressure is low even during strenuous exercise. Generally, the diastolic reserve is large and all the processes of active relaxation, passive filling, and LA contraction are very well organised [55,56].…”
Section: Left Ventricular Diastolic Functionmentioning
confidence: 99%
“…Henein et al [25] showed that, irrespective of LA morphology, LA volume overload because of mitral regurgitation had a less negative effect on intrinsic LA function than pressure overload because of increased LV filling pressure. Athletes with physiologic LV hypertrophy and normal diastolic function have been shown to have lower booster pump function than controls but similar emptying volume because of a larger LA volume [26] without increased stiffness [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, strain value correlates with atrial fibrosis in paroxysmal and persistent AF (Kuppahally et al, 2010). Left atrial deformation assessment has been previously carried out in male and female athletes (D'Andrea et al, 2008; D'Ascenzi et al, 2014, 2015; Sun et al, 2009). However, to our knowledge, there is no study that has determined normal values of LA strain in a large sample of elite athletes.…”
Section: Introductionmentioning
confidence: 99%